Efficient Degradation of Methylene Blue in Industrial Wastewater and High Cycling Stability of Nano ZnO - Ping Liang; Weiye Yang; Hongyan Peng; Shihua Zhao (Molecules)
Photocatalytic degradation research has attracted significant attention in the wake of the increasingly severe global challenge of water pollution. In this study, nano-ZnO was synthesized through a straightforward method using zinc acetate anhydrous as the precursor. The experimental results revealed that annealing conditions significantly influenced the bandgap energy (Eg) of ZnO, with a positive correlation observed between the intensity of photoluminescence (PL) spectra and photocatalytic activity. Under optimal annealing conditions at 300 °C for 1.5 h, the photocatalytic degradation efficiency of methylene blue (MB) exceeded 98% within 40 min of ultraviolet (UV) irradiation, surpassing the efficiencies reported for ZnO in recent studies. This high performance underscores the excellent photocatalytic activity of the synthesized ZnO samples. Furthermore, after five photocatalytic cycles, the degradation efficiency of MB remained above 90%, and the crystalline structure of the ZnO samples remained stable, demonstrating their exceptional structural stability during the photocatalytic process. Additionally, this study examined the effects of stirring conditions and different light sources on MB degradation, providing valuable insights for future research in related fields.